On self-organising mechanisms from social, business and economic domains - Hassas, Salima (Informatica (Ljubljana), 2006)
This paper discusses examples of socially ispired self-organisation approaches and their use to build socially-aware, self-organising computing systems. The paper presents different mechanisms originating from existing social systems, such as stigmergy from social behaviours epidemic spreading, gossiping, trust and reputation inspired by human social behaviours, as well other approaches from social science related to business and economics. It also elaborates on issues related to social network dynamics, social network patterns, social networks analysis, and their relation to the process self-organisation. The applicability of socially inspired approaches in the engineering of self-organising computing systems is then illustrated with applications concerning WWW, computer networks and business communities.
Keywords: business networks; informatika; information science; samoorganizacija; mreže; poslovni sistemi